Slope Map of the Moon's South Pole (85°S to Pole) - Harish; Animireddi, Venkata Satya Kumar; Barrett, Natasha; orcid:0000-0002-4964-1138; Boazman, Sarah; Gawronska, Aleksandra; Gilmour, Cosette; orcid:0000-0002-4978-530X; Halim, Samuel; McCanaan, Kathryn; Shah, Jahnavi; Kring, David A. (David Allen); et al. (Lunar and Planetary Institute, 2019)
This map is based on data collected by the Lunar Orbiter Laser Altimeter (LOLA) onboard the Lunar Reconnaissance Orbiter (LRO). The map shows slopes derived from the LOLA 10-m elevation product (NASA Goddard Space Flight Center; Smith et al., 2010; Smith et al., 2017). The slope is represented with four traditional colors 0° to 5° (light green), 5° to 10° (bright green), 10° to 15° (dark green), 15° to 20° (yellow), and >20° (red). The map covers the region from latitude 85°S to the pole on the rim of Shackleton crater. Slope data are overlain on a derived hillshade with solar azimuth 45°W and solar elevation 45°. Center for Lunar Science and Exploration A product of the Exploration Science Summer Intern Program: Harish, Venkata Satya Kumar Animireddi, Natasha Barrett, Sarah Boazman, Aleksandra Gawronska, Cosette Gilmour, Samuel Halim, Kathryn McCanaan, Jahnavi Shah, and David Kring.